A vision about lifelong learning and its barriers. (17th March 2023) - Conesa, Jordi; Garcia-Alsina, Montserrat; Batalla-Busquets, Josep-Maria; Gómez-Zúñiga, Beni; Martínez-Argüelles, María J.; Monjo, Tona; Mor, Enric; Gil, María Del Carmen Cruz
Around 25 years ago, some researchers argued for moving towards innovative learning models characterised by being more personalised and where the students would have a more active role in deciding what to learn, when to learn and how to learn. Nowadays, there is a need for a flexible, efficient, universal and lifelong education. Lifelong learning is fully integrated into our society and, from the student point of view, it is very different from regular learning. Among these differences there is the maturity of students, the fact that the domains of interest are much broader, the way how learning occurs at different depths, the fact that the topics to study may be related to work, family and leisure, and that students have little availability due to their necessity to conciliate home, work, leisure and learning. Lifelong learning requires personalised models that adapt to students' needs and constraints, but lifelong learners keep suffering from models that are adapted neither to their necessities, nor to the needs of society. This paper reflects on the actual situation of lifelong learning, analyses some of the relevant literature and discusses the challenges to conceptualise, from a transdisciplinary point of view, innovative e-learning models that promote self-determination of students.